Comprehensive Analysis of the Prognostic Value and Immune Infiltration of Butyrophilin Subfamily 2/3 (BTN2/3) Members in Pan-Glioma - He, Dong; Qin, Zhen; Liu, Zihao; Ji, Xiaoshuai; Gao, Jiajia; Guo, Hua; Yang, Fan; Fan, Haitao; Wei, Yanbang; Wang, Zixiao; Liu, Qian; Pang, Qi (Frontiers in Oncology, 2022)
Abstract The BTN2/3 subfamilies are overexpressed in many cancers, including panglioma (low- and high-grade glioma). However, the expression and prognosis of BTN2/3 subfamilies and tumor-infiltrating lymphocytes in panglioma remain unknown. In the present study, we systematically explored and validated the expression and prognostic value of BTN2/3 subfamily members in panglioma (TCGA-GBMLGG merge cohort) using multiple public databases. We used clinical specimens for high-throughput verification and cell lines for qRT–PCR verification, which confirmed the expression profiles of BTN2/3 subfamilies. In addition, the function of the BTN2/3 subfamily members and the correlations between BTN2/3 subfamily expression and panglioma immune infiltration levels were investigated. We found that BTN2/3 subfamily members were rarely mutated. BTN2/3 subfamilies were overexpressed in panglioma; high expression of BTN2/3 subfamily members was correlated with poor prognosis. In addition, BTN2/3 subfamilies might positively regulate proliferation, and the overexpression of BTN2/3 subfamilies influenced cell cycle, differentiation, and glioma stemness. In terms of immune infiltrating levels, BTN2/3 subfamily expression was positively associated with CD4+ T cell, B cell, neutrophil, macrophage, and dendritic cell infiltrating levels. These findings suggest that BTN2/3 subfamily expression is correlated with prognosis and immune infiltration levels in glioma. Therefore, the BTN2/3 subfamilies can be used as biomarkers for panglioma and prognostic biomarkers for determining the prognosis and immune infiltration levels in panglioma. Keywords: BTN/BTNL; BTN2/3; panglioma; immune infiltration